A Novel Bioswitchable miRNA Mimic Delivery System: Therapeutic Strategies Upgraded from Tetrahedral Framework Nucleic Acid System for Fibrotic Disease Treatment and Pyroptosis Pathway Inhibition - Yueying Jiang; Songhang Li; Ruijianghan Shi; Wumeng Yin; Weitong Lv; Taoran Tian; Yunfeng Lin (Advanced Science, 2024)
Abstract There has been considerable interest in gene vectors and their role in regulating cellular activities and treating diseases since the advent of nucleic acid drugs. MicroRNA (miR) therapeutic strategies are research hotspots as they regulate gene expression post‐transcriptionally and treat a range of diseases. An original tetrahedral framework nucleic acid (tFNA) analog, a bioswitchable miR inhibitor delivery system (BiRDS) carrying miR inhibitors, is previously established; however, it remains unknown whether BiRDS can be equipped with miR mimics. Taking advantage of the transport capacity of tetrahedral framework nucleic acid (tFNA) and upgrading it further, the treatment outcomes of a traditional tFNA and BiRDS at different concentrations on TGF‐β‐ and bleomycin‐induced fibrosis simultaneously in vitro and in vivo are compared. An upgraded traditional tFNA is designed by successfully synthesizing a novel BiRDS, carrying a miR mimic, miR‐27a, for treating skin fibrosis and inhibiting the pyroptosis pathway, which exhibits stability and biocompatibility. BiRDS has three times higher efficiency in delivering miRNAs than the conventional tFNA with sticky ends. Moreover, BiRDS is more potent against fibrosis and pyroptosis‐related diseases than tFNAs. These findings indicate that the BiRDS can be applied as a drug delivery system for disease treatment.